Comparative Study of Fig Volatile Compounds Using Headspace Solid-Phase Microextraction-Gas Chromatography/Mass Spectrometry: Effects of Cultivars and Ripening Stages - Zidi, Kahina; Kati, Djamel Edine; Bachir-bey, Mostapha; Genva, Manon; Fauconnier, Marie-Laure (Frontiers in Plant Science, 2021)
Aroma is one of the essential parameters that determine fruit quality. It is also an important feature of varietal characterization and so valuable for agro-biodiversity identification and preservation. In order to characterize changes in the aroma fingerprint through fig development, the main objective of the present research was to study the volatile organic compound (VOC) profiles of figs (Ficus carica L.) from three cultivars, Taamriwthe (TH), Azegzaw (AZ) and Averkane (AV), at three ripening stages (unripe, ripe, and fully ripe). Analysis was performed using Headspace Solid-phase Microextraction and gas chromatography coupled with mass spectrometry. Results revealed the presence of twenty-nine compounds that were grouped into different chemical classes. Aldehydes comprised the most abundant VOCs identified in all the studied figs, while alcohols, ketones, and terpenes comprised the minor compounds found in TH, AZ, and AV figs, respectively. Different aroma descriptors were identified throughout the ripening stages of figs; fruity and green aromas were dominant in all cultivars, while a fatty aroma scarcely occurred in figs. A gallery plot representation demonstrated that certain VOCs differentiate the studied cultivars and the different ripening stages of figs. Principal component analysis findings demonstrated characteristic VOCs of distinct ripening stages and cultivars, those VOCs can be used as fingerprints to distinguish different cultivars and/or ripening stages.